2021
DOI: 10.3390/ijms22136763
|View full text |Cite
|
Sign up to set email alerts
|

Placental Complement Activation in Fetal and Neonatal Alloimmune Thrombocytopenia: An Observational Study

Abstract: Fetal and neonatal alloimmune thrombocytopenia (FNAIT) is a disease that causes thrombocytopenia and a risk of bleeding in the (unborn) child that result from maternal alloantibodies directed against fetal, paternally inherited, human platelet antigens (HPA). It is hypothesized that these alloantibodies can also bind to the placenta, causing placental damage. This study aims to explore signs of antibody-mediated placental damage in FNAIT. We performed a retrospective study that included pregnant women, their n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…They concluded that a higher degree of classical pathway-induced complement activation is present in placentas from pregnancies with untreated FNAIT, which may affect placental function and fetal growth. 34 Further research shall aim to combine indicators of placental inflammation and dysfunction in FNAIT in order to increase our understanding of how the fetal-placental unit modifies disease severity in this disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that a higher degree of classical pathway-induced complement activation is present in placentas from pregnancies with untreated FNAIT, which may affect placental function and fetal growth. 34 Further research shall aim to combine indicators of placental inflammation and dysfunction in FNAIT in order to increase our understanding of how the fetal-placental unit modifies disease severity in this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, de Vos et al, investigating placental complement activation in FNAIT, described a higher degree of C4d deposition in newly diagnosed FNAIT cases, as compared to the IVIg‐treated FNAIT cases or negative controls. They concluded that a higher degree of classical pathway‐induced complement activation is present in placentas from pregnancies with untreated FNAIT, which may affect placental function and fetal growth 34 . Further research shall aim to combine indicators of placental inflammation and dysfunction in FNAIT in order to increase our understanding of how the fetal‐placental unit modifies disease severity in this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…8 A third study identified C4d deposition on syncytiotrophoblasts in 10 of 14 samples from untreated FNAIT cases, including all small for gestational age (SGA) newborns, compared with two of 21 controls, demonstrating likely activation of the classical pathway of complement by IgG binding to the placenta. 9 The fourth study found chronic histiocytic intervillositis in 41% of FNAIT pregnancies compared with none in the 21 controls. 22,7,34 Extensive chronic inflammation (e.g., high-grade chronic villitis) is known to result in fetal growth restriction and SGA newborns.…”
Section: F I G U R Ementioning
confidence: 91%
“…Four studies [7][8][9]22 have identified increased frequency of placental chronic inflammation in HPA-1a-incompatible FNAIT-affected pregnancies, indicating a likely effect of anti-HPA-1a on the placenta and providing a potential mechanism for low neonatal birthweights in FNAIT. HPA-1a is present on GPIIIa (β 3 ), which, in addition to platelets, is found on syncytiotrophoblasts and vascular endothelial cells, where it is expressed in association with α V instead of α ΙΙ (Figure 4).…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation